Development of eco-friendly geopolymer concrete by utilizing hazardous industrial waste materials. (2022) - Suresh Kumar, A.; Muthukannan, M.; Arunkumar, K.; Sriram, M.; Vigneshwar, R.; Gulshan Sikkandar, A.
Abstract: The main objective of this research study is to address the usage of industrial waste materials to increase the environmental friendly geopolymer concrete (GPC), including incinerated bio-medical waste ash (IBWA) and ground granulated blast furnace slag (GGBFS). GGBFS based geopolymer concrete blend was produced and the impact of incorporating IBWA as 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% and 50% replacement by mass of GGBFS, on setting time, flow of concrete, density, air content, compressive strength, split tensile strength, and flexural strength have been examined until the age of ninety days. The results indicate that the setting time and concrete flow are increased and density is decreased with improved utilization of IBWA. However, in contrast to GGBS, IBWA was able to improve the concrete's mechanical properties so that it could be used to act as a substitute for conventional cement and help to mitigate carbon dioxide emissions. IBWA's inclusion resulted in negative results above the optimum content of 30%. Moreover, due to the coexistence of geopolymerization products with extra calcium-based hydration products, the microstructure study's findings indicate a compact and denser geopolymer concrete micrograph at 30% IBWA. The experiments showed that the presence of IBWA could be partly replaced with source material for Geopolymer Concrete. This research may have an effect on the deployment of the hazardous IBWA as a building material.